2007
DOI: 10.1007/s00421-007-0633-2
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the Ramadan fast on physical performance and dietary habits in adolescent soccer players

Abstract: The purpose of this study was to examine the effect of the Ramadan fast on performance capacities, dietary habits, and the daily behavioral patterns in adolescent (14-16-year-old) soccer players. Nineteen male players performed a series of fitness tests before and at the end of Ramadan fast. Caloric intake, physical activity pattern and sleep habits were evaluated during the week before the Ramadan fast and during the last week of the Ramadan fast. The fast resulted in a significant reduction in aerobic capaci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

12
205
9
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(238 citation statements)
references
References 27 publications
12
205
9
2
Order By: Relevance
“…Because Hijra is a lunar calendar, the start of the Islamic year advances 11 days each year compared with the seasonal year, thus Ramadan occurs at different times of the seasonal year over a 33-year cycle. Sporting competitions and the associated training that is required of serious athletes continue to be scheduled throughout the month of Ramadan (Meckel, Ismaeel, & Eliakim, 2007;Zerguini, Kirkendall, Junge, & Dvorak, 2007). Although the perception of many coaches and sportspeople is that the Ramadan fast negatively affects sports performance, there is little scientific evidence to support this suggestion.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Because Hijra is a lunar calendar, the start of the Islamic year advances 11 days each year compared with the seasonal year, thus Ramadan occurs at different times of the seasonal year over a 33-year cycle. Sporting competitions and the associated training that is required of serious athletes continue to be scheduled throughout the month of Ramadan (Meckel, Ismaeel, & Eliakim, 2007;Zerguini, Kirkendall, Junge, & Dvorak, 2007). Although the perception of many coaches and sportspeople is that the Ramadan fast negatively affects sports performance, there is little scientific evidence to support this suggestion.…”
Section: Introductionmentioning
confidence: 94%
“…Only three studies (Bouhlel et al, 2006;Meckel et al, 2007;Zerguini et al, 2007) have examined the impact of Ramadan on top athletes, but they did not include a non-fasting control group during the period of Ramadan. The aim of the current study was to account for the complexity of the effects of fasting compared with a non-fasting population during the same time with the same physical activities among elite football players.…”
Section: Introductionmentioning
confidence: 97%
“…During the month of Ramadan, Food and fluid intake frequency and quantity are decreased and those qualities are changed to the consumption of foods that contain more carbohydrates and starches. Also sleep and physical activity habits are changed as reduction (Meckel et al, 2008). It is important to know the effect of this kind of fasting on people's life especially with or without exercise.…”
Section: Introductionmentioning
confidence: 99%
“…The role of Ramadan on physical performance is contentious [ 20 ] . Meckel et al [ 21 ] observed that while repeated sprint performance was reduced, maximal single sprints eff orts were maintained during Ramadan. Similarly, intermediate (10 m) sprint time was unaff ected 2 weeks into Ramadan, while overall repeated 30 m sprint times were shown to decrease [ 16 ] .…”
mentioning
confidence: 97%
“…However, physical activity patterns over the same time frame have not been fully elucidated. In athletes, it has been reported that training volume is maintained [ 8 ] , and that the quantity of intense exercise is reduced during Ramadan [ 21 ] . However, the existence of modifi cations in spontaneous activity over the entire 24 h of the day in the general population (i.e.…”
mentioning
confidence: 99%